Genome-Wide Assessment of Runs of Homozygosity and Estimates of Genomic Inbreeding in a Chinese Composite Pig Breed - Xu, Zhong; Mei, Shuqi; Zhou, Jiawei; Zhang, Yu; Qiao, Mu; Sun, Hua; Li, Zipeng; Li, Lianghua; Dong, Binke; Oyelami, Favour Oluwapelumi; Wu, Junjing; Peng, Xianwen (Frontiers in Genetics, 2021)
The aim of this study was to assess the genetic diversity, runs of homozygosity (ROH) and autozygosity islands in a composite pig to explore hotspot regions for traces of selection. In this study, we estimated the number, length and frequency of ROH in 262 Xidu black pigs using the Porcine SNP50 BeadChip and compared estimates of inbreeding coefficients calculated based on ROHs (FROH) and homozygosity (FHOM). A total of 7248 ROH exceeding 1 Mb were detected in 262 animals. In addition, Sus scrofa chromosome (SSC) 8 and SSC10 exhibited the highest and lowest coverage of chromosomes by ROH, respectively. The results of this study suggest that inbreeding based on total ROH may be a useful method, especially for crossbreed or composite populations. An inbreeding coefficient of 0.077 was calculated from total ROH. Eight regions were found to contain ROH islands. These ROH islands harbored genes associated with fat deposition, muscular development, reproduction, ear shape and adaptation, such as TRAF7, IGFBP7, XPO1, SLC26A8, PPARD, OR1F1. These findings contribute to the understanding the genetic diversity of composite pigs and the effects of artificial selection in shaping the distribution of functional variants in the pig genome.